ANALISIS PENGARUH UPAH,PDRB,DAN INVESTASI TERHADAP PENYERAPAN TENAGA KERJA DIKAWASAN GERBANGKERTASUSILA TAHUN 2012-2016 - Nofandillah Arumsyah Putri; Aris Soelistyo (Jurnal Ilmu Ekonomi JIE, 2018)
This research aims to analyze the influence of wages , PDRB , and Investment on employment absortion. Dependent variabel used is labor , and Independent variabel used is panel data , a combination of time series and cross section. This research uses six districts / cities ini Gerbangkertasusila area ini 2012-2016. This estimation results show that the wage variable has a negatif effect of -0.069927 and significant , PDRB variable also has negatif effect of -0.253666 and significant , while investment variable has a positive effect on labor absortion of 0.599640 and significant. In the selection of the best model in this research is to use the Random Effect Model (REM), choosing a Random Effect Model because thus model has a Standart error smaller than the Common Effect Model (CEM).Keyword : Wage ,PDRB , Investment , Labor.